2021
DOI: 10.4102/sajhivmed.v22i1.1200
|View full text |Cite
|
Sign up to set email alerts
|

Undisclosed exposure to antiretrovirals prior to treatment initiation: An exploratory analysis

Abstract: Background: The proportion of individuals with a history of exposure (‘pre-exposure’) to antiretrovirals (ARVs) prior to formal initiation into antiretroviral treatment (ART) is unknown.Objectives: This study describes the detection of ARVs in plasma and/or hair, of persons who self-reported no pre-exposure to ART at their first-time initiation onto ART in three clinics in the province of Limpopo, South Africa (SA).Method: Concentrations of tenofovir (TDF), emtricitabine (FTC) and efavirenz (EFV) in the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Discordance proportions and agreement between self-report and laboratory detection were in keeping with a similar study conducted in the Kwazulu-Natal province, however non-disclosure of ART status (2.9%) was notably lower in our cohort compared to this study [9]. Several other studies in sub-Saharan Africa comparing self-report and biomarkers of current or previous ART use showed higher proportions of ART non-disclosure, however these studies had smaller sample sizes and the study population was not restricted to pregnant women presenting for antenatal care [18][19][20][21]. While the study by Huerga et.…”
Section: Discussionsupporting
confidence: 86%
“…Discordance proportions and agreement between self-report and laboratory detection were in keeping with a similar study conducted in the Kwazulu-Natal province, however non-disclosure of ART status (2.9%) was notably lower in our cohort compared to this study [9]. Several other studies in sub-Saharan Africa comparing self-report and biomarkers of current or previous ART use showed higher proportions of ART non-disclosure, however these studies had smaller sample sizes and the study population was not restricted to pregnant women presenting for antenatal care [18][19][20][21]. While the study by Huerga et.…”
Section: Discussionsupporting
confidence: 86%
“…The setting, inclusion criteria and baseline characteristics for these studies were clearly defined. Mavhandu-Ramarumo (2019)19, Lebelonyane (2020)12, Dorward et al 21, Barnabas et al 18 and Sithole et al 20 also sufficiently defined inclusion criteria, study setting and baseline characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Discordance proportions and agreement between self-report and laboratory detection were in keeping with a similar study conducted in the Kwazulu-Natal province, however non-disclosure of ART status (2.9%) was notably lower in our cohort compared to this study (8.1%) [ 9 ]. Several other studies in sub-Saharan Africa comparing self-report and biomarkers of current or previous ART use showed higher proportions of ART non-disclosure, however these studies had smaller sample sizes and the study population was not restricted to pregnant women presenting for antenatal care [ 21 24 ]. While the study by Huerga et al in Kwazulu Natal found younger individuals were at higher risk of discordance, our study found no demographic risk factors for discordance [ 9 ].…”
Section: Discussionmentioning
confidence: 99%